IN VITRO ASSESSMENT OF ETHANOLIC EXTRACT OF CUCUMIS MADERASPATANUS LEAVES AS AN α-AMYLASE AND α-GLUCOSIDASE INHIBITOR - NADHIYA K; MAHALAKSHMI P; KALAIVANI P (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The current study was planned to study the phytochemicals, Antioxidant, and inhibitor activity of alpha-glucosidase and alpha-amylase from leaf extract of Cucumis maderaspatanus. Methods: Extract was extracted using a soxhlet apparatus using solvents, such as n-hexane, chloroform, ethyl acetate, ethanol, and aqueous. The extracts were evaporated using a rotary evaporator. The phytochemicals were measured qualitatively and quantitatively and the antioxidant activity was done and the IC50 value was calculated. Result: The qualitative analysis of the ethnolic leaf extract of C. maderaspatanus shows the presence of carbohydrates, terpenoids, phenol compounds, tannins, saponins, flavonoids, alkaloids, anthocyanins, betacyanins, quinones, glycosides, sterol, and coumarins. Quantitative analysis of ethanolic leaf extract of C. maderaspatanus showed that the presence of phenols (98.63±0.03), flavonoids (80.35±0.78), saponin (16.56±0.04), alkaloids (12.56±0.05), and total antioxidant (130.18±2.45). The IC50 value of various parameters such as DPPH (IC50=265), Nitric oxide (IC50=213), Hydrogen peroxide (IC50=355), Hydroxyl (IC50=290), Superoxide (IC50=145), alpha-amylase activity (IC50=48), and alpha-glucosidase activity (IC50=76). Conclusion: From the study, it was concluded that the ethanolic leaf extracts of C. maderaspatanus have good antioxidant capacity, alpha-amylase, and alpha-glucosidase inhibitor activity due to phytochemicals present in it.